Morphometric and gonad maturity of the spider crab Libinia ferreirae Brito Capello, 1871 (Decapoda: Majoidea: Epialtidae) on the south-eastern Brazilian coast - Goncalves, Geslaine Rafaela Lemos [UNESP] (2017)
Sexual maturity of the spider crab Libinia ferreirae was assessed for each sex, based on body dimensions and observations of gonad condition. A total of 346 crabs were analysed, of which 68% were females. Immature and adult individuals were recognized based on their allometric growth and gonad development. Abdomen width (AW) vs carapace width (CW) and propodus length (PL) vs CW were the relationships that best separated allometric groups of females and males, respectively. For females, gonad and allometric morphological maturity were, respectively, 38.77 and 39.43 mm of CW, which is close to the carapace size of the smallest ovigerous female (38.08 mm). For males, gonad maturity was 34.86 mm of CW and three allometric phases were observed: immature (IM male), adolescent (AD) and adult morphometrically mature (MM male). The IM male phase showed lower values of CW and PL than the AD male phase, without spermatophores inside the vas deferens; the AD male phase exhibited higher CW values than IM male, but lower CW and PL values than the MM male phase, and the presence of spermatophores in the vas deferens; the MM male phase had higher values of CW and PL than the AD male phase and spermatophores in the vas deferens. Therefore, females showed synchronic morphometric, gonadal and functional maturity, while in males, gonadal maturity was attained before morphometric maturity, which probably could be a reproductive strategy for this species.